Brominated oxime nucleophiles are efficiently reactivating cholinesterases inhibited by nerve agents - Prchalova, Eliska; Andrys, Rudolf; Pejchal, Jaroslav; Kohoutova, Zuzana; Knittelova, Karolina; Hofmanova, Tereza; Skarka, Adam; Dlabkova, Alzbeta; Psotka, Miroslav; Prchal, Lukas; Musilek, Kamil; Karasova, Jana Zdarova; et al. (Archives of toxicology, 2024)
Six novel brominated bis-pyridinium oximes were designed and synthesized to increase their nucleophilicity and reactivation ability of phosphorylated acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Their pKa was valuably found lower to parent non-halogenated oximes. Stability tests showed that novel brominated oximes were stable in water, but the stability of di-brominated oximes was decreased in buffer solution and their degradation products were prepared and characterized. The reactivation screening of brominated oximes was tested on AChE and BChE inhibited by organophosphorus surrogates. Two mono-brominated oximes reactivated AChE comparably to non-halogenated analogues, which was further confirmed by reactivation kinetics. The acute toxicity of two selected brominated oximes was similar to commercially available oxime reactivators and the most promising brominated oxime was tested in vivo on sarin- and VX-poisoned rats. This brominated oxime showed interesting CNS distribution and significant reactivation effectiveness in blood. The same oxime resulted with the best protective index for VX-poisoned rats.
Keywords: pyridinové sloučeniny; oximy; Nerve Agents; Drug Stability; Nucleophile; Pyridinium Compounds; halogenace; Oximes; Reactivation; chemické bojové látky; organothiofosforové sloučeniny; Organophosphate; nervová bojová látka; krysa rodu Rattus; Oxime; Nerve agent; zvířata; Cholinesterase; potkani Wistar; cholinesterasové inhibitory; sarin; Organothiophosphorus Compounds; Rats, Wistar; butyrylcholinesterasa; Male; Halogenation; Acetylcholinesterase; reaktivátory cholinesterasy; Cholinesterase Reactivators; Sarin; Rats; stabilita léku; Animals; Chemical Warfare Agents; mužské pohlaví; Butyrylcholinesterase; acetylcholinesterasa; Cholinesterase Inhibitors